Neolithic Shrine (2022)
The article reports that a research from the French Institute of the Near East and Jordan's Al-Hussein Bin Talal University discovered a Neolithic hunting traps in Jordan's southeastern desert near the site of Jibal al-Khashabiyeh. It mentions the traps were used extensively throughout prehistoric southwestern Asia, and the unique ritual complex, which dates to around 7000 B.C.E., resembles a miniature desert kite, and anthropomorphic stone figures.
Keywords: ANIMAL traps; DRY stone walls; Jordan; Neolithic period; Shrines